Hubungan Kualitas Sistem, Informasi, Dan Layanan Terhadap Kepuasan Pengguna Sistem Manajemen Informasi Rumah Sakit Di RSUD Kembangan Jakarta - Putri Rafikasani; Puteri Fannya; Muniroh Muniroh; Laela Indawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
One of the regional hospitals in Kembangan type D, West Jakarta, is District General Hospital Kembangan. The information management hospital (HMIS) is now used by the District General Hospital Kembangan to provide services.A number of issues exist, such as the fact that the Simrs server is still frequently prone to errors and slow service processes and reporting; data loss occurs when user data is transferred to another unit; insufficient computer resources; and a shortage of human resources to utilize the HMIS's features due to the hospital's lack of knowledge about how to run an effective HMIS. Analyzing system quality, information quality, and service quality in relation to customer happiness is the goal of this study.There are three independent variables and one dependent variable in this categorical study design.According to the findings, there is a correlation between user happiness and the quality system of (p = 0.031).Quality information and user happiness are related, as indicated by the statistic (p = 0,240).User happiness and quality of service are related, as indicated by the statistic (p = 0,021).The study's findings indicate that there is a correlation between customer satisfaction surveys and the quality of the system, information, and services.